Childhood Maltreatment, Limbic Dysfunction, Resilience, and Psychiatric Symptoms. Issue 1 (January 2020) - Ashy, Majed; Yu, Brian; Gutowski, Ellen; Samkavitz, Anna; Malley-Morrison, Kathleen
Previous research has indicated that childhood maltreatment is predictive of psychiatric symptoms in adulthood. Among the potential intervening factors in this relationship are affective reactions in the victims, neurodevelopmental problems, and resilience. The purpose of this study was to test, in a nonclinical low-risk sample, an integrative developmentally based psychoneurological model of the roles of limbic system dysfunction, shame and guilt, and resiliency as potential intervening variables between childhood maltreatment and adult psychiatric symptoms. Also of interest was whether there were gender-specific pathways from maltreatment to symptoms. Based on the results of preliminary analyses, several regressions were conducted separately by gender, entering the different forms of parental aggression at Step 1, resilience at Step 2, the resilience by parental aggression interaction term at Step 3, shame and guilt at Step 4, and limbic dysfunction at Step 5, as predictors of psychiatric symptoms. Analyses indicated that both maternal psychological maltreatment and paternal physical maltreatment were predictive of total psychiatric symptomatology in adulthood, with shame mediating the relationship in women and guilt mediating it in men, limbic system symptoms mediating the relationship in both genders, and trait resilience moderating the relationship in both genders.